STANDARDIZATION: CONCEPT AND RESULTS - BLIŪDŽIUVIENĖ, NIJOLĖ (Knygotyra, 2015)
The article outlines development of standardization, presents details of academic disputes about standardization as a scholarly discipline and introduces basic standardization concepts.The main focus is on the international level of standardization activity. While various types of standards are discussed, de jure standards adopted by the International Standardization Organization (ISO) and de facto standards drafted by international organizations of library, archival and museum communities are given major coverage. Relationship between de jure and de facto standards, mostly applied by documentation institutions, is defined and examples of such standards are provided.In all times, the standard has been an instrument of serving certain social needs. Social benefit of standards is therefore highlighted when assessing the importance of standardization in the global context of contemporary knowledge and technologies. However, in addition to social effects of standardization, the economic and psychological factors come into play as well. Recent challenges brought about by the modern knowledge age and new technologies tend to overcome institutional differences. Libraries, museums, and archives are launching various joint projects and thus interdisciplinary communication is being expanded.Considering disappearance of boundaries between institutions in the digital space, an agreement on application of common standards by memory institutions could serve as a medium of their integration, despite their diverse practices.
Keywords: ...